Prevalence and associated factors of acute postoperative pain in adult surgical patients: A prospective study - Eyob Asefa Bekele; Tseganesh Berhanu Tulu; Yonathan Abebe Bulto; Gebeyehu Tessema Azibte; Waltengus Birhanu (Surgery in Practice and Science)
Background: Pain, as defined by the International Association for the Study of Pain, is an unpleasant sensory and emotional experience associated with, or resembling, that is associated with actual or potential tissue damage. In Ethiopia, where healthcare facilities and offerings are expanding to handle countless patients requiring surgical intervention, managing acute postoperative pain is a serious concern. Objectives: To assess the prevalence of acute postoperative pain and associated factors after elective surgery among adult patients at Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia, 2023 Methodology: This is an institution-based cross-sectional study. A structured data collection format was used to collect data from 219 participants. Bivariable and multivariable logistic regression analyses described the association between independent and dependent variables. Results: Of 219 patients, 180 (82.2 %) had acute postoperative pain. The prevalence of moderate to severe pain was 34.24 %. Preoperative anxiety, the use of intraoperative analgesics, and duration of surgery were the main factors associated with the prevalence of acute postoperative pain. Conclusion: Our study revealed that the overall prevalence of postoperative pain was relatively low in the study area. This suggests that the attention given to postoperative pain recognition and management is better than that in other areas. However, the finding of a significant gap in managing postoperative pain underscores the need for further improvements in pain management practices. This should motivate us to commit to change, particularly in the identified areas of concern, such as preoperative anxiety, use of intraoperative analgesics, and duration of surgery.